Post QALY: Scientific Approaches to Real World Formulary Decision Making - Paul Langley; Stephen McKenna (University of Minnesota Libraries Publishing, 2020)
The purpose of this anniversary supplement for Innovations in Pharmacy is to consider and / or propose modern, scientific methods for determining the evidence base for the fair pricing and accessibility of pharmaceutical products and medical devices. At present, such decisions are based on the construction of imaginary value assessment models that fail to meet the standards of normal science. Such a business model has been adopted by the Institute for Clinical and Economic Review (ICER) in the US, NICE in the UK and in a number of other countries.   Article Type: Call for Papers